2009
DOI: 10.1038/ng.388
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide and fine-resolution association analysis of malaria in West Africa

Abstract: We report a genome-wide association (GWA) study of severe malaria in The Gambia. The initial GWA scan included 2,500 children genotyped on the Affymetrix 500K GeneChip, and a replication study included 3,400 children. We used this to examine the performance of GWA methods in Africa. We found considerable population stratification, and also that signals of association at known malaria resistance loci were greatly attenuated owing to weak linkage disequilibrium (LD). To investigate possible solutions to the prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
365
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 360 publications
(388 citation statements)
references
References 37 publications
17
365
2
4
Order By: Relevance
“…Other factors such as population structure and chance, as well as the experimental design or the phenotype(s) of malaria diagnosed in a given study, may impact the conclusions. Efforts to use genomics approaches and genome-wide association analysis have been initiated (Ayodo et al, 2007;Timmann et al, 2007;The Malaria Genomic Epidemiology Network, 2008;Jallow et al, 2009;Eid et al, 2010) and some new regions of potential malaria resistance have been identified.…”
Section: Resistance Mutantsmentioning
confidence: 99%
“…Other factors such as population structure and chance, as well as the experimental design or the phenotype(s) of malaria diagnosed in a given study, may impact the conclusions. Efforts to use genomics approaches and genome-wide association analysis have been initiated (Ayodo et al, 2007;Timmann et al, 2007;The Malaria Genomic Epidemiology Network, 2008;Jallow et al, 2009;Eid et al, 2010) and some new regions of potential malaria resistance have been identified.…”
Section: Resistance Mutantsmentioning
confidence: 99%
“…The ethnic-specific distribution of two of these blood group variants, Sl1/2 (Lys/Glu 1590 at the CCP24-25 junction) and McC a/b (Arg/Gly 1601 in CCP25) has been proposed to result from selective pressures in malarial endemic regions of Africa. However, contradictory results have been obtained regarding their association with malarial severity in different African populations (52)(53)(54)(55). CR1 interacts with two P. falciparum proteins, the malarial adhesin PfEMP1 (14) and the PfRh4 invasion ligand (15), but the binding sites have been located to the C3b and C4b binding sites of CR1, respectively (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…For several common infectious diseases, susceptibility loci with moderate to large effect sizes (at-risk odds ratios 41.5) were successfully identified by GWAS. For example, associations have been identified between HbS and malaria 5 and between CFH locus and infection by Neisseria meningitides. 6 Recently, a GWAS of two African TB populations identified a gene desert in 18q11.2 as a novel candidate locus for TB, but unlike GWASs in other common infectious diseases, GWASs of TB were not successful in identifying any genetic factors with moderate to large effect sizes.…”
Section: Introductionmentioning
confidence: 99%